ARCHAEOLOGY - Fagan, Brian M., author. ([S.l.])
1 online resource
Keywords: Archaeology is a jargon-free and accessible introduction to the field which details how archaeologists study the human past in all its fascinating diversity. Now in its thirteenth edition, this classic textbook has been updated to include the latest research and new findings in the field. Reflecting the global scope of the discipline, the book has a truly international coverage of important discoveries and sites from many corners of the globe. Individual chapters examine archaeology and its history, considering the role of the archaeologist and how they discover, investigate and classify sites and artifacts. This journey through archaeology also includes a discussion of important individuals and groups, and some of the ways in which archaeologists attempt to explain major social and cultural changes in the remote past. Archaeology ends with an outline of the complex world of cultural resource management and gives invaluable advice on how to become an archaeologist. Richly illustrated throughout, this popular and engaging textbook on archaeological methods has introduced generations of students to the captivating world of archaeology.